Tendências pedagógicas, metodológicas de ensino e avaliação no ensino fundamental: entre projetos político-pedagógicos e discursos docentes - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The Brazilian public elementary school is in crisis and its students have been getting very disappointing results in external assessments, such as Programme for International Student Assessment (PISA), Prova Brasil and the Basic Education Assessment System. This indicates that students learning levels do not seem to be being effectively achieved. Still, in the context of the outskirts of the city of Alegrete- RS, some schools have been attaining some success in achieving the goals proposed by the national government in relation to the Basic Education Development Index. This research aimed to identify the pedagogical trends (LIBÂNEO, 2014) present in the political-pedagogical projects (PPP) of the schools and in the teachers’ speeches to seek relations between the results obtained and the trends practiced in different schools, emphasizing aspects of methodology and evaluation. This work consists of a research of multiple case studies, with qualitative analysis. For this, we initially built a systematic review to know the scientific production about the evaluation aspects present in PPP of public schools in Brazil. Then, we studied the political-pedagogical projects of these schools, seeking to understand the pedagogical perceptions that prevail in each one. Next, we seek to understand the pedagogical theories that support the teachers' discourse through a questionnaire. The analysis of the obtained data was instrumentalized from different strategies related to the content analysis (BARDIN, 1977). The school PPPs presented general characteristics closely related to the progressive renewed liberal pedagogy with sporadic manifestations of liberating progressive pedagogy. Regarding the teachers, their pedagogical trends were briefly divergent in some aspects, but, considering the whole group, the predominant tendencies were the progressive renewed liberal and the technician liberal. With regard specifically to teaching methodologies and assessment, school PPPs have retained the same characteristics, while teachers’ speeches has turned even more to the teacher as keeper of knowledge as it stands out from traditional and technician liberal trends. Thus, we inferred that the grounding in pedagogical theories dating back to the early and mid-last century reflects the difficulty of education in renewing its pedagogical practices based on pedagogical trends aimed at the social emancipation of students and consequent capacity for transformation of established political-social relations. In addition, we understand that there is a need for greater proximity and interaction between academy and elementary school in order to appropriate the problems at school by university and, especially, to expand the repertoire of elementary school through the acquisition of new pedagogical conceptions of the academic environment and their suitability for your specific needs.
Pedagogical, methodological teaching and evaluation trends in elementary education: between political-pedagogical projects and teaching discourses
Keywords: Pedagogical trends; Political-pedagogical project; Teachers’ speeches; Teaching methodologies; Learning assessment; Tendências pedagógicas; Projeto político-pedagógico; Discurso docente; Metodologias de ensino; Avaliação da aprendizagem; CNPQ::CIENCIAS HUMANAS